2012
DOI: 10.1371/journal.pone.0049422
|View full text |Cite
|
Sign up to set email alerts
|

Novel Diabetic Mouse Models as Tools for Investigating Diabetic Retinopathy

Abstract: ObjectiveMouse models possessing green fluorescent protein (GFP) and/or human aldose reductase (hAR) in vascular tissues have been established and crossed with naturally diabetic Akita mice to produce new diabetic mouse models.Research Design and MethodsColonies of transgenic C57BL mice expressing GFP (SMAA-GFP), hAR (SMAA-hAR) or both (SMAA-GFP-hAR) in vascular tissues expressing smooth muscle actin were established and crossbred with C57BL/6-Ins2Akita/J (AK) mice to produce naturally diabetic offspring AK-SM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 57 publications
1
20
0
Order By: Relevance
“…This has resulted in naturally diabetic mice (AK-SMAA-GFP-hAR) that demonstrate increased retinal AR activity compared to similar mice not expressing hAR. Here, we report that the retinal growth factor and signaling changes as well as vascular lesion changes that we have demonstrated in AK-SMAA-GFP-hAR mice (Kador et al, 2012) are more similar to changes observed in diabetic rats than mice not expressing aldose reductase.…”
Section: Introductionsupporting
confidence: 53%
See 4 more Smart Citations
“…This has resulted in naturally diabetic mice (AK-SMAA-GFP-hAR) that demonstrate increased retinal AR activity compared to similar mice not expressing hAR. Here, we report that the retinal growth factor and signaling changes as well as vascular lesion changes that we have demonstrated in AK-SMAA-GFP-hAR mice (Kador et al, 2012) are more similar to changes observed in diabetic rats than mice not expressing aldose reductase.…”
Section: Introductionsupporting
confidence: 53%
“…The development of the AK-SMAA-GFP-hAR transgenic mice and their genotyping has previously been reported (Kador et al, 2012). In the AK-SMAA-GFP-hAR group initial blood glucose levels ranged from 247–600 mg/dL for females and 342–600 mg/dL for males and in the AK-SMAA-GFP group blood glucose levels ranged from 245–572 mg/dL for females and 332–600 mg/dL for males.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations